Outcasts and Rivals: Stereotypes of Single Mothers in the Media and Life Stories - Latinytė, Rūta (Tautosakos darbai, 2025)
The article examines the personal experiences of single mothers and the surrounding public opinion and media environment, which both reflects and influences the world mothers live in. Single mothers, as a vulnerable group in society, are associated with stereotypes and prejudices in the media and in comments from relatives. It is true that until now most topics related to motherhood, fatherhood, and family structure are usually studied separately in the fields of sociology, family policy, law and psychology, but the disciplines of ethnology and cultural anthropology could provide a deeper look into being a single mother and offer a more complex analysis, showing how social, psychological, legal and communication aspects are closely interconnected and experienced in individual situations. For the research, I analyzed media content and collected personal life stories of single mothers in the form of interviews about their daily experiences and how their environment affects them. Here, I analyze excerpts from nine such interviews and my own articulated experience, delving deeper into it from the perspective of semiotic and phenomenological anthropology. The aim of the analysis is to reveal how these experiences are expressed and what personal, social and cultural aspects they may reveal, thus seeking to better understand the phenomenon of being a single mother.
Keywords: single mother; motherhood; stereotypes; research on everyday practices; phenomenological anthropology; media content analysis